Incisor torque expression characteristics in two passive self-ligating brackets placed at different heights. A finite element investigation - R.P Bernisha; Gyanda Mishra; G. Pradeep Raj; Prasad Chitra (Elsevier, 2024)
Objective: This study investigated torque expression in maxillary incisors using two passive self-ligating bracket types (Damon Q and Pitts 21) placed at different heights using the Finite element method. Materials and methods: Two passive self-ligating brackets, Damon Q (Ormco, USA) and Pitts 21 (OC Orthodontics, USA) were 3D modeled using micro-computed tomography. Damon Q (0.022ˮ x 0.028" slot size) and Pitts 21 (0.021ˮ x 0.021" slot size) brackets were placed on a maxillary central incisor at predetermined vertical heights. Arch wires of size 0.019ˮ x 0.025" stainless steel (Damon Q) and 0.020ˮ x 0.020" Titanium Molybdenum (Pitts 21) were placed in the bracket slots. Results: Pitts 21 brackets showed higher torquing moments at all bonding heights as compared to Damon Q brackets. The minimum torquing moment was 9.03Nmm at 5 mm for Damon Q and the maximum torquing moment was 14.92Nmm for Pitts 21 at a bracket bonding height of 8 mm. Total deformation for Pitts 21 at a height of 5 mm from the incisal edge was 0.61 × 10−6mm as compared to that of Damon Q which was 0.41 × 10−6mm. Lowest Von Mises stress values were at 27.07 MPa in Damon Q brackets at a bracket height of 5 mm from the incisal edge. Highest Von Mises stress values were 36.80 MPa for Pitts 21 brackets at a bracket height of 8 mm from the incisal edge. Conclusion: Pitts 21 brackets exhibited superior torquing characteristics compared to Damon Q. Total deformation in Pitts 21 was higher than Damon Q at all tested bracket bonding heights.